Geostandards and Geoanalytical Research Bibliographic Review 2017. Issue 4 (30th November 2018) - Weis, Ulrike; Kaiser, Viktoria; Leisgang, Isabelle; Nohl, Uwe; Reichstein, Anna; Schwager, Beate; Stoll, Brigitte; Zwillich, Florentine; Jochum, Klaus Peter
Key Points: Literature review for 2017 of 8700 geoanalytical publications. Geochemical and environmental reference materials. A total of 752 selected articles with summaries of target analytes, and relevant reference materials and producers.